Perbedaan Derajat Keasaman Kulit Wajah, Dada dan Punggung Pada Penderita Akne Vulgaris di Kota Medan Tahun 2019 - br. Sembiring, Yuni Selfiana; Panjaitan, Rudyn Reymond; Nababan, Kristo A (Nommensen Journal of Medicine, 2021)
Background: Acne vulgaris is a disease of the pilosebaceous unit that often occurs in adolescents and young adults. The pathogenesis of acne vulgaris involves several factors, one of which is the acidity (pH) of the skin. Objective: This study aimed to determine the difference in the degree of acidity of facial skin, chest and back of patients with acne vulgaris. Methods: This was a comparative analytic study with cross sectional design. The sample collection technique was consecutive sampling. Data were analyzed using ANOVA-test. Results: The majority of patients with acne vulgaris who came to Murni Teguh Memorial Hospital Medan and the private clinic of dr. Rudyn Reymond Panjaitan, M.Ked (KK), Sp.KK was a 17-25 year old. The mean acidity of facial skin with acne vulgaris was 5.66, the mean acidity of chest skin was 5,84 and the mean acidity of back skin was 6.09. There was a significant difference in the mean value of acidity in facial, chest and back skin of patients with acne vulgaris (p = 0,000). Conclusion: There is a significant difference in average degree of acidity on the facial, chest and back skin in patients with acne vulgaris.